Digitalisasi sebagai upaya adaptif industri pasar modal di era disruption: dampak pada eksistensi WPPE di masa pandemi Covid-19 - Edi Murdiyanto; Taufik Akbar; Ati Retna Sari (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2021)
This research is based on the number of securities companies that have begun to focus on the phenomenon of their business on online services, both online account opening and online trading media transactions as an effort to adapt to the current disruption. The research was conducted with a qualitative approach, by triangulating research data. Not all data were obtained in full due to limited access obtained by researchers. From the results of the study, there was an increase in the number of investors in the capital market during the COVID-19 pandemic. On the other hand, there is a decrease in the number of securities companies that are members of the stock exchange, as well as the WPPE licensed brokerage profession which is facing serious challenges due to this phenomenon.